Globalization and Inequality Revisited - Galbraith, James K. (Central and Eastern European Economic Review, 2017)
This article summarizes the literature on inequality and economic development from Kuznets (1955) through the neo-classical labor-market-adjustment models and technology/education dialectics of the 1990s, and onward to the modern use of comprehensive, consistent data sets with global coverage to assess the interdependent and divergent experience of advanced, developing and transition economies in the age of globalization. Work based on the data sets developed by the University of Texas Inequality Project broadly validates Kuznets’ original view of the importance of inter-sectoral transitions, but with many distinct and new insights, as it becomes possible to track regional and transnational patterns, common global macroeconomic forces and, most recently, the critical role played by exchange rates in the evolution of inequality in open economies.